Electrical Coupling Between Cells and Graphene Transistors. Issue 14 (19th November 2014) - Hess, Lucas H.; Becker‐Freyseng, Christoph; Wismer, Michael S.; Blaschke, Benno M.; Lottner, Martin; Rolf, Felix; Seifert, Max; Garrido, Jose A.
<x xml:space="preserve">Abstract</x> In this work, both experimental data and a model are presented on the coupling between living cells and graphene solution‐gated field‐effect transistors. Modified HEK 293 cells are successfully cultured on graphene transistor arrays and electrically accessed by the patch clamp method. Transistor recordings are presented, showing the opening and closing of voltage‐gated potassium ion channels in the cell membrane. The experimental data is compared with the broadly used standard point‐contact model. The ion dynamics in the cell–transistor cleft are analyzed to account for the differences between the model and the experimental data revealing a significant increase in the total ionic strength in the cleft. In order to describe the influence of the ion concentration resulting from the cell activity, the ion‐sensitivity of graphene solution‐gated field‐effect transistors is investigated experimentally and modelled by considering the screening effect of the ions on the surface potential at the graphene/electrolyte interface. Finally, the model of the cell–transistor coupling is extended to include the effect of ion accumulation and ion sensitivity. The experimental data shows a very good agreement with this extended model, emphasizing the importance of considering the ion concentration in the cleft to properly understand the cell‐transistor coupling.